Management of Inclusive Education Institutions (A Case Study of an Inclusive Education Provider’s Primary School in Bandung and Sidoarjo City, Indonesia) - Umi Safiul Ummah; Akhlis Priya Pambudy (International Journal of Social Sciences & Educational Studies, 2017)
This study aims at describing management covering curriculum, student management, facilities and infrastructure management, personnel management and education, financial management, school relationship management with the community, and special service management. This research employed descriptive qualitative method using case study. This research was conducted at school X in Bandung city and school Y in Sidoarjo city. The data collection was done by conducting observation, interview, and document study. The data were then analyzed based on qualitative data analysis with case study in nature according to Milles and Huberman. The findings showed the curriculum used in both schools were different in terms of curriculum preparation, management of learners, facilities and infrastructure of both schools include learning media and school accessibility is not fully supportive, time management of educators and education-administrator for employee recruitment. Another aspect being described is about finance sources and school tuition, and also the policy related to students with special needs. In short, the results showed both schools applying inclusive values, yet those aspects need improvement.